2010
DOI: 10.1099/vir.0.022293-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the major tegument protein pp65 of human cytomegalovirus inhibits virus growth and leads to the enhancement of a protein complex with pUL69 and pUL97 in infected cells

Abstract: The tegument protein pp65 of human cytomegalovirus (HCMV) is abundant in lytically infected human foreskin fibroblasts (HFF), as well as in virions and subviral dense bodies (DB). Despite this, we showed previously that pp65 is dispensable for growth in HFF. In the process of refining a DB-based vaccine candidate, different HCMV mutants were generated, expressing a dominant HLA-A2-presented peptide of the IE1 protein fused to pp65. One of the mutant viruses (RV-VM1) surprisingly showed marked impairment in vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…In line with previous studies, phase-contrast images of cells infected with RV-VM1, but not with the wild-type parental strain RV-HB5, showed that NIBs (nuclear inclusion bodies) were undetectable in the majority of the infected nuclei and replaced by large globular structures (LGS) (Fig. 8A), both of which are considered sites of virus replication, transcription, and capsid assembly (33). Indirect immunofluorescence staining using a pp65 MAb demonstrated the nuclear retention of mutant pp65, especially at 144 hpi in cells infected with RV-VM1 (Fig.…”
Section: Viral Pp65 Interacts With Ifi16 During Late Stages Of Hcmv Isupporting
confidence: 64%
See 2 more Smart Citations
“…In line with previous studies, phase-contrast images of cells infected with RV-VM1, but not with the wild-type parental strain RV-HB5, showed that NIBs (nuclear inclusion bodies) were undetectable in the majority of the infected nuclei and replaced by large globular structures (LGS) (Fig. 8A), both of which are considered sites of virus replication, transcription, and capsid assembly (33). Indirect immunofluorescence staining using a pp65 MAb demonstrated the nuclear retention of mutant pp65, especially at 144 hpi in cells infected with RV-VM1 (Fig.…”
Section: Viral Pp65 Interacts With Ifi16 During Late Stages Of Hcmv Isupporting
confidence: 64%
“…The RV-HB5 virus was originally cloned by inserting a BAC vector into the US2-US6 gene region of the AD169 strain (35,36). The HCMV mutant RV-VM1, expressing nuclear pp65, is a descendant of RV-HB5 and was produced as previously reported (33). Briefly, pp65 in RV-VM1 carries a 30-amino-acid insertion at Arg387 that encompasses an immunodominant HLA-A2-presented peptide from the nonstructural IE1 protein (comprising amino acids 288 to 309) and a myc tag.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…RV-KB14 (28,32), which fail to produce subviral DBs; and additionally, two viral mutants, RV-SB2 and RV-VM1, in which pp65 was modified by insertion of a nonapeptide sequence at positions S101 and R387, respectively (33,34). DB formation is also abrogated in HFF infected with RV-SB2 and RV-VM1 (33,34). RV-VM1-infected HFF display wt pp65 steady-state protein levels (33), whereas RV-SB2 (a pp65low strain)-infected cells show a marked reduction in pp65 levels in relation to other virion proteins (Fig.…”
Section: Purification Of Hcmv Virions For Proteomic Analysismentioning
confidence: 99%
“…The pp65neg strain RV-KB14 was generated by inserting a tetracycline resistance cassette into the UL83 (pp65) ORF of pAD/cre (the BAC clone used for reconstitution of RV-BADwt), thereby deleting the pp65-coding region except for 152 5= base pairs of the ORF (32). The mutants RV-SB2 and RV-VM1 were generated by inserting the nonapeptide TMYGGISLL from the immediate-early 1 (IE1) protein of HCMV at position S101 or R387, respectively, of pp65, using galK-mediated recombination on the BACmid pHB5 (33,34). All viruses were characterized previously with respect to their genomic structures and biological properties.…”
Section: Cells and Virusesmentioning
confidence: 99%